Prevalence and Incidence of Hepatitis C Virus in Hemodialysis Patients in British Columbia: Follow-up after a Possible Breach in Hemodialysis Machines. Issue 2 (2009) - Tu, Andrew W; Buxton, Jane A; Whitlock, Mandy; Djurdjev, Ognjenka; Chong, Mei; Krajden, Mel; Beaulieu, Monica; Levin, Adeera
Abstract : BACKGROUND: A possible breach of the transducer protector in specific dialysis machines was reported in June 2004 in British Columbia (BC), which led to testing of hemodialysis patients for hepatitis C virus (HCV), hepatitis B virus (HBV) and HIV. This testing provided an opportunity to examine HCV incidence, prevalence and coinfection with HBV and HIV, and to compare anti-HCV and HCV polymerase chain reaction (PCR). METHODS: The results of hemodialysis patients who were dialyzed on the implicated machines (65% of BC dialysis patients), and tested for HCV, HBV and HIV, between June 1, 2004, and December 31, 2004, were reviewed and compared with available previous results. RESULTS: Of 1286 hemodialysis patients with anti-HCV and/or HCV-PCR testing, 69 (5.4%) tested positive. Two HCV genotype 4 seroconversions were identified. HCV incidence rate on dialysis was 78.8 cases per 100, 000 person-years. Younger age, history of renal transplant and past HBV infection were associated with HCV infection. No occult infection was identified using HCV-PCR. INTERPRETATION: Hemodialysis patients had three times the HCV prevalence rate of the general BC population, and more than 20 times the incident rate of the general Canadian population. One of the two seroconversions occurred before the testing campaign; the patient was likely infected during hemodialysis in South Asia. The other was plausibly a late seroconversion following renal transplant in South Asia. Nosocomial transmission cannot be ruled out because both patients were dialyzed in the same centre. Baseline and annual anti-HCV testing is recommended. HCV-PCR should be considered at baseline for persons with HCV risk factors, and for returning travellers who received dialysis in HCV-endemic countries to identify HCV infection occurring outside the hemodialysis unit.